Food prices and inflation in Tanzania - Adam, C; Kwimbere, D; Mbowe, W; O'Connell, S (African Finance and Economic Association, 2017)
This paper presents an econometric model of headline Tanzanian inflation and its principal components for the period since 2000. Inflation is modeled in terms of deviations from a set of ‘anchors’ reflecting long-run demand-side and monetary determinants, on the one hand, and supply-side and open economy factors on the other. Five main conclusions derive from our analysis. First, money growth and hence the stance of monetary policy matters for inflation both in the long run and in the short run. Second, however, the principal component of overall inflation -- food price inflation -- is predominantly driven by supply-side factors including both domestic agricultural output shocks and by the passthrough from world prices for food and fuel. Third, the effect of domestic supply conditions on food price inflation points to the asymmetric effects of trade policy in Tanzania; while food imports appear to respond reasonably rapidly to domestic production short-falls, the capacity to export surplus food production is much more muted so that market adjustment in this case occurs through falling prices, other things equal. Fourth, headline inflation exhibits strong seasonality, consistent with weak price-stabilizing effects of trade and incomplete storage. Non-food inflation is, by contrast, broadly non-seasonal. Finally, prices in Tanzania in general are flexible, more so for the food and energy subcomponents but even in the traditionally sticky-price domain of core inflation there is little evidence of inflation persistence overall. Some channels of price adjustment are take time – notably the effects of monetary disequilibrium -- but in general inflationary shocks dissipate rapidly with half-live being little more than one month.